Towards a universal master curve in magnetorheology. (6th April 2017) - Ruiz-López, José Antonio; Hidalgo-Alvarez, Roque; de Vicente, Juan
Abstract: We demonstrate that inverse ferrofluids behave as model magnetorheological fluids. A universal master curve is proposed, using a reduced Mason number, under the frame of a structural viscosity model where the magnetic field strength dependence is solely contained in the Mason number and the particle concentration is solely contained in the critical Mason number (i.e. the yield stress). A linear dependence of the critical Mason number with the particle concentration is observed that is in good agreement with a mean (average) magnetization approximation, particle level dynamic simulations and micromechanical models available in the literature.